PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, LEVERAGE DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN - Gabrielle Givens Kurniawan Ardiansyah (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
This study aims to obtain empirical evidence on the influence of profitability, firm size, leverage, and liquidity on firm value in manufacturing companies listed in Indonesia Stock Exchange in the period 2015-2017. Research samples are 62 companies out of 166 companies data using purposive sampling method. Result of this research obtained the profitability, firm size and leverage have positive effect to firm value. Whereas, the liquidity have no effect to firm value.